Youth physical activity profile: A gender perspective - Rusdiawan, Afif; Wiriawan, Oce; Kusuma, Donny Ardy; Firmansyah, Awang; Mohamad Nor, Azmawaty; Ar Rasyid, Labib Siena (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to assess gender differences and correlates of physical activity (PA) among children in East Java, Indonesia. An observational population-based cross-sectional study was conducted on a representative sample of children (n = 900, mean age 13.27±0.97) in East Java. The instrument used in this study was the Children’s Physical Activity Questionnaire, which measured the level of physical activity with high reliability (Kappa = 0.67–0.73) and moderate validity (r = 0.48). Boys reported higher engagement than girls in sport activities, school activities, and other activities, all differences being statistically significant (p = 0.000). Leisure time activities were slightly higher in boys, but this difference was not significant (p = 0.083). Overall CPAQ scores were also higher in boys (2.51 vs. 2.33, p = 0.000), indicating that boys generally had higher levels of physical activity than girls. In conclusion, girls are less likely than boys to engage in PA. Therefore, there is a need to consider the provision of a comprehensive multifaceted health behavior modification and interventions, such as targeted and regular physical education in schools.